Solusi Persamaan SchröDinger Osilator Harmonik Dalam Ruang Momentum - Paken Pandiangan (Jurnal Matematika Sains dan Teknologi, 2005)
The solution of Schrödinger equation for the simple harmonic oscillator has been investigated and explored. The solutions are coordinate representation or momentum representation. The eigen energy is . The expectation value is respectively. Both Method will produce similar result.